2006
DOI: 10.1099/mic.0.28692-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoethanolamine substitution in the lipid A of Escherichia coli O157 : H7 and its association with PmrC

Abstract: This study shows that lipid A of Escherichia coli O157 : H7 differs from that of E. coli K-12 in that it has a phosphoform at the C-1 position, which is distinctively modified by a phosphoethanolamine (PEtN) moiety, in addition to the diphosphoryl form. The pmrC gene responsible for the addition of PEtN to the lipid A of E. coli O157 : H7 was inactivated and the changes in lipid A profiles were assessed. The pmrC null mutant still produced PEtN-modified lipid A species, albeit in a reduced amount, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
(56 reference statements)
1
34
0
Order By: Relevance
“…Also, pEtN substitution was observed in an enterohemorrhagic E. coli strain (EHEC; see Fig. 3A) (24). In our study, lipid A variants were observed in APEC strains but not in porcine ExPEC strains under low-phosphate conditions.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Also, pEtN substitution was observed in an enterohemorrhagic E. coli strain (EHEC; see Fig. 3A) (24). In our study, lipid A variants were observed in APEC strains but not in porcine ExPEC strains under low-phosphate conditions.…”
Section: Discussionsupporting
confidence: 50%
“…Since the pst mutants display PMB sensitivity, which could be caused by lipid A modifications (18,35,45), we undertook radiolabeled lipid A analyses by TLC. Because of its known TLC profile, an E. coli O157:H7 strain was used as a control (24). Its profile is similar to that of E. coli K-12 MC1061 except for an additional phosphoethanolamine (pEtN) lipid A variant (24) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of the 4Ј position of the lipid A moiety of LOS (or LPS) with PEA is known to confer resistance to cationic antimicrobial peptides such as polymyxin B on N. meningitidis (41), Salmonella enterica (23), and E. coli (21). However, other biological roles of the modification have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid A backbone structure is highly conserved in most bacteria, but it is also remodeled by the addition or subtraction of components in response to environmental cues (Needham and Trent 2013). For example, covalent modification of phosphate groups in the lipid A by the addition of positively charged moieties, such as phosphoethanolamine (Kim et al 2006;Raetz et al 2007), galactosamine (Wang et al 2009), glucosamine (Marr et al 2008) and 4-amino-4-deoxy-L-arabinose (L-Ara4N) (Trent, Ribeiro, Doerrler, et al 2001;Molinaro et al 2015), reduce the overall negative charge of the molecule. These covalent modifications confer resistance to cationic antimicrobial peptides such as polymyxin B (PmB) and aminoglycoside antibiotics, and are associated with enhanced bacterial virulence (Needham and Trent 2013).…”
Section: Introductionmentioning
confidence: 99%